The The Potential of Curcuma longa as an Antidiabetic Agent: Review: The Potential of Curcuma longa as an Antidiabetic Agent: Review - Rosyid Ridho, Muhammad Ainur; Indriani, Ratri Dwi (Direktorat Riset dan Pengabdian Kepada Masyarakat, Institut Teknologi Sepuluh Nopember, 2025)
Diabetes mellitus (DM) is a chronic metabolic disease characterized by persistently elevated blood sugar levels due to impaired insulin action or production. It is a global health concern, contributing to various complications such as retinopathy, neuropathy, and cardiovascular diseases. While antidiabetic medications have improved treatment options, challenges such as adverse effects, resistance, and high costs have fueled the interest in exploring natural alternatives, including Curcuma longa, commonly known as turmeric. This review aims to evaluate the potential of Curcuma longa as an antidiabetic agent by synthesizing data from existing literature. A systematic search of databases including PubMed, Scopus, Web of Science, and Google Scholar was conducted, focusing on studies from 2000 to 2024 that examined the pharmacological effects, mechanisms of action, and clinical applications of Curcuma longa in diabetes. The review highlights that curcumin, the active compound in Curcuma longa, significantly reduces blood glucose levels, improves insulin sensitivity, and exhibits anti-inflammatory and antioxidant properties. Curcumin acts through multiple mechanisms, including the modulation of glucose transporters, activation of AMPK, reduction of oxidative stress, and inhibition of inflammatory cytokines. Preclinical and clinical studies demonstrate that curcumin can improve glycemic control, reduce insulin resistance, and prevent diabetes-related complications. Despite promising results, further clinical trials are needed to confirm its therapeutic potential. This review underscores the potential of Curcuma longa as a natural adjunct or alternative to conventional antidiabetic therapies.